STATUS AND PROSPECTS OF LABOR MARKET DEVELOPMENT IN THE CONDITIONS OF TRANSFORMATION OF SOCIETY AND ECONOMY OF UKRAINE - KAPINOS, HENNADII; LARIONOVA, KATERINA (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article identifies current problems of the globalized labor market of Ukraine, the main of which are a significant decline in the economically active population, reduced employment in all regions of the country, rising unemployment and labor migration, aging society, economic restructuring, falling economic growth, informatization of society. The defining approach to solving these problems is the integration of workers into the digitalized labor market, which is developing dynamically in recent years compared to the traditional market. The article presents the results of research on the current state of the labor market in Ukraine and personnel management processes in it in terms of comprehensive digitalization, taking into account the output of the new "digital generation". in 2014-2021 and especially during the COVID-19 pandemic, the level of unemployment and migration, transformational processes in society and the economy and their impact on the formation and development of the labor market are analyzed. The main characteristics of the new "digital generation" are studied. Due to the fact that the labor market is significantly transformed and there is a need to restructure all components of the personnel management system of economic entities, the article considers the latest trends in labor and which they must have to meet the modern requirements of employers. Scientific and practical recommendations for the effective integration of the Ukrainian labor market into the process of digitalization of the global economy have been developed. The main tendencies that will form the sphere of future labor relations in the new digital labor market are systematized.
Keywords: labor market; digitalization; unemployment; the new digital generation; population migration